(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2024)
In order to better understand non-verbal and kinesics, this article examines the language and concepts used in scientific sources. Studying non-verbal cues including posture, touch, eye contact, gestures, and facial expressions is crucial since linguistics is not just about spoken communication. Understanding nonverbal cues is crucial for analyzing cultural differences